A Civic Ethics in Kant? - Pinzani, Alessandro (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
The paper investigates whether there is space in Kant’s practical thought for juridical morality and for political virtues. To this end, we will first discuss the Doctrine of Method of the second Critique and consider the possible existence of a moral schematism analogous to the transcendental schematism of the first Critique. We will then consider differences and similarities between Kant’s doctrine of right and his ethics, in order to ponder the question whether one can assert the possibility of political and civic virtues in his political thought.